Bentuk Penyajian Tari Ramo-Ramo Tabang Duo Di Nagari Pasir Talang - Widya Novitri; Indrayuda Indrayuda (FBS Universitas Negeri Padang, 2020)
This article aims to describe the Presentation Form of the Ramo-ramo Tabang Duo Dance in Nagari Pasir Talang. This research is a qualitative study using descriptive methods. The object of research is the presentation of the Ramo-ramo Tabang Duo dance in Nagari Pasir Talang Solok Selatan. The researcher acts as the main instrument in this study, and is assisted by a recording device, and a means of matching both audio, visual or audio visual. Data collection is done through direct observation, interviews, and documentation, as well as literature studies. Data were analyzed through a procedure referred to from Mile and Huberman, namely data collection, in the form of qualitative data from research areas such as forms of motion, music, costumes, and procedures for performance. In the next stage the data is selected and then the results of the selection are verified and concluded by the researcher. The findings from the research results are concluded that the form of presentation of the Ramo-ramo Tabang Duo dance is an artistic form without a story. This is obtained from the motion data that only presents artistic and aesthetic value, without any symbol of the motion being maneuvered, as well as music that is as a dance accompaniment. Overall both motion, music, and costumes display dynamical, dramatic motion that aims only as a presentation of entertainment, without any intention of the dance performance.